Geological risk and reservoir quality in hydrocarbon exploration - Xia, Changyou (The University of Edinburgh, 2018)
In the next 20 years, the global demand for oil is forecast to grow by 0.7% every year, and the demand for natural gas will increase by 1.6% annually. But as we continue to produce oil and gas, the resources of our current oilfields are depleting. To meet the rising global energy demand, it is essential that we can keep discovering more petroleum resources in the future. The primary aim of this PhD project is to deepen our understanding of hydrocarbon reservoirs and enhance our ability to explore. The first project looked at the geological risks in hydrocarbon exploration. It reviewed and statistically analysed the data of 382 unsuccessful boreholes in the UK offshore area. The results suggest that the most significant risk for an exploration well is encountering a thin or absent target reservoir. This risk happened to 27 ± 4% of the past unsuccessful wells. The following most common risks are low-porosity reservoirs (22 ± 4% of all cases) and the lack of a closed trap (23 ± 4%). The probability of a target reservoir having a leaky caprock is 5 ± 2%. The study has calculated the probability of occurrence of all the geological risks in exploration, and this risk data can be applied to predict the potential geological risks in future exploration. One challenge in developing saline aquifers as CO2 storage reservoirs is the lack of subsurface data, unless a well has been drilled. Drawing on the experience of hydrocarbon exploration, a potential CO2 storage site identified on seismic profiles will be subject to many uncertainties, such as thin or low-porosity reservoirs, leaky seals, which are analogue to the geological risks of an undrilled hydrocarbon prospect. Since the workflow of locating CO2 storage reservoirs is similar to the exploration for hydrocarbon reservoirs, the risk data of hydrocarbon exploration wells can be applied to infer the geological risks of the exploration wells for CO2 storage reservoirs. Based on this assumption, the study of Chapter 3 estimated that the probability of a borehole encountering a reservoir suitable for CO2 storage is c. 41–57% (90% confidence interval). For reservoirs with stratigraphic traps within the UKCS, the probability of success is slightly lower, at 39 ± 10% (90% confidence). Chapter 4 studies the porosity and diagenetic process of the Middle Jurassic Pentland Formation in the North Sea. The analysis data come from 21 wells that drilled and cored the Pentland Formation. Petrographic data suggest the content of detrital illite is the most important factor affecting the porosity of the Pentland Sandstone - the porosities of the sandstones with more than 15% of illite (determined by point-count) are invariably low (< 10%). Quartz cement grows at an average rate of 2.3 %/km below the depth of 2km, and it is the main porosity occluding phase in the deep Pentland Sandstone. Petrographic data shows the clean, fine-grained sandstones contain the highest amount of quartz cement. Only 1-2 % of K-feldspar seems to have dissolved in the deep Pentland Sandstone (> 2 km), and petrographic data suggest that K-feldspar dissolution does not have any substantial influence on the sandstone porosity. There is no geochemical evidence for mass transfer between the sandstones and shales of the Pentland Formation. Chapter 5 investigates the high porosity of the Pentland Sandstone in the Kessog Field, Central North Sea. The upper part of the Kessog reservoir displays an anomalously high porosity (c. 25 %, helium porosity) that is 10 % higher than the porosity of other Pentland sandstones at the same depth (c. 15 %, 4.1 - 4.4 km). Petrographic data show these high porosities are predominantly primary porosity. The effects of sedimentary facies, grain coats, secondary porosity and overpressure on the formation of the high porosity are considered to be negligible in this case. Early hydrocarbon emplacement is the only explanation for the high porosity. In addition to less quartz cement, the high-porosity sandstones also contain more K-feldspar and less kaolin than the medium-porosity sandstones of the same field. This indicates that early hydrocarbon emplacement has also inhibited the replacement of K-feldspar. The last chapter studies the potential mass transfer of silica, aluminium, potassium, iron, magenesium and calcium at sandstone-shale contacts. The study samples include 18 groups of sandstones and shales that were collected from five oilfields in the North Sea. The interval space between the samples of each group varies from centimetres to meters. The research aim is to find evidence of mass transfer by studying the samples’ variation of mineralogy and chemistry as a function of the distance to the nearest sandstone-shale contact. The sandstones are mostly turbidite sandstones, and the shales are Kimmeridge Clay shales. Petrographic, mineralogical and chemical data do not provide firm evidence for mass transfer within any group of the samples. The result indicates that the scale of mobility of silica, aluminium, potassium, iron, magenesium and calcium in the subsurface may be below the scale of detection of the study method, i.e. < 5 cm.
Keywords: geological risk; hydrocarbon exploration; sandstone diagenesis; North Sea; reservoir quality